2021
DOI: 10.3389/fdgth.2021.798889
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Smart Home in a Box to Monitor the Wellbeing of Residents With Dementia in Care Homes

Abstract: There is a global challenge related to the increasing number of People with Dementia (PwD) and the diminishing capacity of governments, health systems, and caregivers to provide the best care for them. Cost-effective technology solutions that enable and ensure a good quality of life for PwD via monitoring and interventions have been investigated comprehensively in the literature. The objective of this study was to investigate the challenges with the design and deployment of a Smart Home In a Box (SHIB) approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Telephone, computer, or video supports can help caregivers through these difficult times. Substantial progress has been made recently to aid both formal and informal caregiving [ 56 , 57 , 58 , 59 , 60 ], thus this may be an avenue to contemplate with future research in combination with findings from this study. However, further research is needed on caregivers’ views, with a solutions-based approach that will identify caregivers’ problems and at the same time will provide possible solutions to address these based on the perceived needs of the caregiver.…”
Section: Discussionmentioning
confidence: 94%
“…Telephone, computer, or video supports can help caregivers through these difficult times. Substantial progress has been made recently to aid both formal and informal caregiving [ 56 , 57 , 58 , 59 , 60 ], thus this may be an avenue to contemplate with future research in combination with findings from this study. However, further research is needed on caregivers’ views, with a solutions-based approach that will identify caregivers’ problems and at the same time will provide possible solutions to address these based on the perceived needs of the caregiver.…”
Section: Discussionmentioning
confidence: 94%
“…As the study was conducted during the pandemic (2021), solely fully vaccinated (validated vaccination certificates with verified app) participants were recruited. Moreover, after each participant's visit decontamination by experts took place at the SH to ensure the safety of all people involved.…”
Section: Aim Of the Present Workmentioning
confidence: 99%
“…A plethora of sensors has been used and deployed in the context of Smart Homes (SH) (in the sense of controlled research environments, care homes or participants’ homes where the sensors are being installed) allowing for remote in-home sensing and remote ADL monitoring ( Garcia-Constantino et al, 2021 ; Moyle et al, 2021 ). There are many opportunities for the use of various SH technologies in community-dwelling PwD, ranging from diagnostic assessment to long-term and personalized care management.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluated diabetes patients' activity, diet, and exercise compliance in SHT settings and observed that SHT settings are essential in providing accessible, low-cost health assistance in an individual's home and providing the best possible quality of life [15]. In contrast, an SHT developed and tested in laboratory settings to monitor the well-being of elderly residents with dementia in care homes was unable to be deployed in real time due to infrastructure deficiencies [16]. On the other hand, designing SHT in consultation with dementia patients, their caregivers, clinicians, and health and social care service providers to satisfy the functional, psychosocial, and environmental needs results in the development of SHT that provide patient-centric interventions and assist in seamlessly transitioning to clinical practice and public health strategy [17].…”
Section: Introductionmentioning
confidence: 99%